SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN BIBIT POHON SINGKONG MENGGUNAKAN METODE MULTIFACTOR EVALUATION PROCESS (MFEP) (STUDI KASUS DESA BANTARSARI KABUPATEN BOGOR) - Juniar Puspasari; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Bantarsari Village is located in Bogor Regency from a very promising plantation sector, namely cassava is the main product and is a mainstay, almost in every resident's house there must be a cassava tree. Therefore cassava farmers must be able to sort out good cassava tree seeds in order to produce healthy trees, so they can get good results for sale or become beautiful when used as tourist attractions. Decision support systems that are currently developing have various methods, one of which is using the MFEP method. The purpose of this research is how to use the MFEP method as an alternative for decision makers in determining good cassava seeds to be planted by farmers so they can produce fresh trees and fruit. Rapid Application Development (RAD) is a method of developing an information system with a relatively short time. With the development of this system, it helps farmers in Bantarsari Village, Kab. Bogor in making decisions to determine cassava tree seeds that are in accordance with good nursery results quickly and efficiently. Researchers successfully implemented a decision support system using the Multifactor Evaluation Process (MFEP) method.